2006
DOI: 10.1161/01.hyp.0000198543.34502.d7
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Arginase I Restores NO Signaling in the Vasculature of Old Rats

Abstract: Abstract-Arginase, expressed in endothelial cells and upregulated in aging blood vessels, competes with NO synthase (NOS) for L-arginine, thus modulating vasoreactivity and attenuating NO signaling. Moreover, arginase inhibition restores endothelial NOS signaling and L-arginine responsiveness in old rat aorta. The arginase isoform responsible for modulating NOS, however, remains unknown. Because isoform-specific arginase inhibitors are unavailable, we used an antisense (AS) oligonucleotide approach to knockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
138
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(152 citation statements)
references
References 48 publications
10
138
3
1
Order By: Relevance
“…Two additional NO synthase isoforms exist in mammals, neuronal NO synthase (nNOS; encoded by Nos1) and endothelial NO synthase (encoded by Nos3), which may benefit from L-citrulline metabolism. Arginase activity regulates NO output in endothelial cells during hypertension and in aged rodents (31)(32)(33). Furthermore, it was suggested that endothelial NO synthase relies on L-arginine synthesis from L-citrulline to mediate optimal NO production (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Two additional NO synthase isoforms exist in mammals, neuronal NO synthase (nNOS; encoded by Nos1) and endothelial NO synthase (encoded by Nos3), which may benefit from L-citrulline metabolism. Arginase activity regulates NO output in endothelial cells during hypertension and in aged rodents (31)(32)(33). Furthermore, it was suggested that endothelial NO synthase relies on L-arginine synthesis from L-citrulline to mediate optimal NO production (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…For RT-PCR, total RNA from rat heart and isolated myocytes was prepared by homogenization in the presence of Trizol reagent (GIBCO), and RT-PCR was performed with specific Arg I and II primers, as described (52).…”
Section: Methodsmentioning
confidence: 99%
“…NO production was evaluated by measuring nitrite levels (Calbiochem) after preincubation of heart and myocytes with BEC (10 mol͞liter) in PBS (pH 7.4), as described (52).…”
Section: Methodsmentioning
confidence: 99%
“…The main functions of endothelial cells include the inhibition of blood coagulation, control of vascular wall tension, control of angiogenesis and inflammatory and immune processes. In light of the role of the epithelium in both the synthesis and release of several hormonal compounds, it may be considered to be the largest endocrine organ in the human body [54]. The principal substances released by endothelial cells include [51,54]:  endothelin 1 -responsible, e.g., for vasoconstriction,  prostacyclin -responsible primarily for vasodilatation and inhibition of platelet aggregation,  nitrogen oxide (NO) -responsible for vasodilation, inhibition of platelet aggregation and inhibition of platelet adhesion,  von Willebrand factor (vWF) -stimulating blood coagulation and platelet adhesion,  tissue thromboplastin and thrombomodulin -activating blood coagulation,  interleukins (IL-2, IL-3, IL-6) -responsible for proliferation and differentiation of immune system cells,  tissue plasminogen activator (TPA) -responsible for the control of fibrinolysis.…”
Section: Endothelium -Histological Structure and Significancementioning
confidence: 99%
“…They activate antithrombin, heparin co-factor, the lipoprotein lipase, inhibitors of the exogenous clotting system and platelet factor 4. Upon analysis of the ultrastructure, endothelial cells were seen to form junctions with the assistance of cadherin 5 (CD144) and MACAM-1 (CD146) [54]. Integrin receptors are manifested in their basolateral parts, which bind the endothelium to components of the basement membrane and extracellular matrix, with collagen, glycosaminoglycans, fibronectin, elastin, vitronectin, laminin or thrombospondin.…”
Section: Endothelium -Histological Structure and Significancementioning
confidence: 99%